Acetoclastic methane formation from Eucalyptus detritus in pristine hydrocarbon‐rich river sediments by Methanosarcinales. Issue 3 (15th September 2014) - Beckmann, Sabrina; Manefield, Mike
Abstract Pristine hydrocarbon‐rich river sediments in the Greater Blue Mountains World Heritage Area (Australia) release substantial amounts of methane. The present study aimed to unravel for the first time the active methanogens mediating methane formation and exploiting the bacterial diversity potentially involved in the trophic network. Quantitative PCR of 16S rRNA gene and functional genes as well as 454 pyrosequencing were used to address the unknown microbial diversity and abundance. Methane‐releasing sediment cores derived from three different river sites of the Tootie River. Highest methane production rates of 10.8 ± 0.5 μg g−1wet weight day−1 were detected in 40 cm sediment depth being in congruence with the detection of the highest abundances of the archaeal 16S rRNA gene and the methyl‐coenzyme M reductase (mcrA) genes. Stable carbon and hydrogen isotopic signatures of the produced methane indicated an acetoclastic origin. Long‐term enrichment cultures amended with either acetate or H2/CO2 revealed acetoclastic methanogenesis as key methane‐formation process mediated by members of the order Methanosarcinales. Conditions prevailing in the river sediments might be suitable for hydrocarbon‐degrading bacteria observed in the river sediments that were previously unclassified or closely related to the Bacteroidetes/Chlorobi group, the Firmicutes and the Chloroflexi group fuelling acetoclastic methanogensis in pristine river sediments.